An Exploratory Study of the Change of the British Society\'s Attitude towards Homosexuality - Fatima Zahra Amraoui; Abbès Bahous (Université de Laghouat , Bibliothèque centrale, 2015)
Homosexuality has become one of the vogue subjects of the twenty first century in Britain. Some believe it is a sin, others claim that it is a way of life and for them love is not confined within the limits of the opposite sex, for others it is a disease from which one can be cured. The purpose of this paper is to explore the British society’s attitudes towards homosexuality throughout history. The paper is borne out of concern on how the British public opinion has swayed, throughout history, from condemning homosexuality, which they deemed as a vice, to categorizing it as a psychological disorder, and finally recognizing it as choice of life. By British society, I mean people, religion, politics, medical viewpoint, culture, and the media. The study will explore the historical background of homosexuality in Britain, and will discuss the Bible’s position via-à-vis the subject. The phenomenon of homosexuality will be explored from the psychological point of view, by explaining the subject from different theories, and examining the influence of these theories on the British public attitude. The shift from pro to anti and from anti to pro homosexuality during the twentieth century will also be dealt with and examined. Finally the paper will investigate the role of the media in the twenty first century in molding the public’s stance towards homosexuality, the extent to which recognition means acceptance of the studied phenomenon in the British society, and the influence of culture on homosexuality and on homosexual intellectuals and vice versa.